FACTORS AFFECTING THE GAP IN TAX RECEIVABLE REVENUES - Omid Hajati, Hassan Farazmand, Seyed Morteza Afghah, Seyed Aziz Arman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present study aimed to investigate factors affecting the tax gap from an economic, social, political and organizational perspective in Khuzestan province. To this end, the theoretical foundations and empirical studies were used to estimate the tax capacity model, according to which the tax gap model was developed using a variety of variables, including tax rate and inflation (economic factors), Gini coefficient (social factor), political stability (political factor), and tax audit (organizational factor). The estimation results of the tax capacity model revealed that the tax effort exhibits no stable trend, and that the tax received by the Tax Affairs Organization presents uncertain and fluctuating behaviors. Moreover, the estimation results of the tax gap model suggested that the tax gap decreased with increasing audit capability in the Tax Affairs Organization. Furthermore, enhanced inflation also increased the tax gap, and the tax gap decreases with increasing political stability. However, despite compliance with theoretical principles, the relationship between the Gini coefficient and the tax gap was not significant at p=0.05. Accordingly, income inequality in the province is not expected to affect the tax gap. According to the findings, the relationship between the tax rate and the tax gap was positive and significant; hence, the tax gap in the province is expected to raise with an increase in the tax rate.